The impact of the divergent programmed learning strategy on creative thinking and learning key defensive skills in volleyball - Habib, L.Dr.Ahmed Radhi; Abdul-Ridha, Asst.L.Uday Hatem; Amir, Asst.L. Shaimaa Ali Abdul (Sulaimani Journal for Humanities, 2025)
Branched programmed learning develops the student's ability to self-direct and empowers them to assume responsibility for decision-making. Therefore, this learning process is a modern, systematic approach that fosters interaction between the student and the program presented to them, without direct influence from the teacher. It is one of the technological methods in the field of teaching and motor learning methods, which saves the teacher effort and time in explaining the educational material. Hence, the importance of the research lies in understanding the impact of the strategy used in learning the most important defensive skills in volleyball. The researchers noted that learning defensive skills in volleyball depends on the educational situation that is appropriate for the type of skill to be learned, as well as the nature of the learner. Not every skill requires the same method. The skills of receiving the serve and defending the court require a method that attracts the learner's attention and allows them to follow the learning process to achieve the correct performance, especially when they feel that the difficulty of the skill may distract them and distract them from concentrating on learning the skill. Therefore, the idea of introducing a learning strategy related to his creative thinking and focusing his attention as a scientific step came to be an actual contribution in implementing the process of learning difficult motor skills and the most important goals are to identify the effect of the branched programmed learning strategy on creative thinking and learning the most important defensive skills in volleyball. The researchers used the experimental method, and by designing a method of two equivalent groups (experimental and control) with pre- and post-tests because it is compatible with the research problem, the research community was identified, represented by fifth-grade students in Muslim bin Aqeel Intermediate School for Boys in Najaf Governorate for the academic year (2024-2025) with a number of (140) students. The most important conclusions were the superiority of the experimental group using the branched programmed learning strategy that was taught in developing creative thinking and learning the skills (receiving the serve and defending the field) in volleyball for students. The most important recommendations are to include the cross-programmed learning strategy in in-service teacher training programs, in order to inform teachers of the feasibility of this strategy and the extent to which it can be used in the educational process.